The Internal Control System and Good Corporate Governance on Fraud Prevention in The National Road Planning and Supervision Unit of The Province of South Sumatra in 2022. - Della Ayu Lestari; Lili Syafitri; Mutiara Kemala Ratu (ProBisnis : Jurnal Manajemen, 2023)
This research is a quantitative research that aims to determine the effect ofthe internal control system, good corporate governance on the prevention of fraudin the Work Unit for Planning and Supervision of National Roads of South SumatraProvince. The data used in this research is primary data in the form of a questionnaire. The method used in this research is multiple linear regression analysis. The results of this study indicate that the internal control system variablehas a positive effect on fraud prevention. Good corporate governance has anegative effect on preventing fraud in the Planning and Supervision Work Unit forthe National Roads of South Sumatra Province in 2022.